2005
DOI: 10.1158/0008-5472.can-04-2345
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Endothelial Growth Factor-A Promotes Peritumoral Lymphangiogenesis and Lymphatic Metastasis

Abstract: Metastases are commonly found in the lymphatic system.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
128
1
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 172 publications
(137 citation statements)
references
References 32 publications
6
128
1
2
Order By: Relevance
“…The first type of new blood vessel to form in response to Ad-VEGF-A 164 has a characteristic morphology and has been given the name 'mother vessel' (MV) (Pettersson et al, 2000). However, similar MV-like blood vessels are also induced by polymers containing VEGF-A 164 or basic fibroblast growth factor (Cao et al, 1998) and by tumours expressing VEGF-A or basic fibroblast growth factor and plateletderived growth factor-BB (Paku and Paweletz, 1991;Bjorndahl et al, 2005;Nagy et al, 2007;Nissen et al, 2007). The other types of angiogenic vessels evolve from MVs and thus may be properly regarded as 'daughter' vessels ( Figure 1) (Pettersson et al, 2000;Dvorak, 2003;Nagy et al, 2007).…”
Section: How Do Tumour Blood Vessels Form?mentioning
confidence: 99%
“…The first type of new blood vessel to form in response to Ad-VEGF-A 164 has a characteristic morphology and has been given the name 'mother vessel' (MV) (Pettersson et al, 2000). However, similar MV-like blood vessels are also induced by polymers containing VEGF-A 164 or basic fibroblast growth factor (Cao et al, 1998) and by tumours expressing VEGF-A or basic fibroblast growth factor and plateletderived growth factor-BB (Paku and Paweletz, 1991;Bjorndahl et al, 2005;Nagy et al, 2007;Nissen et al, 2007). The other types of angiogenic vessels evolve from MVs and thus may be properly regarded as 'daughter' vessels ( Figure 1) (Pettersson et al, 2000;Dvorak, 2003;Nagy et al, 2007).…”
Section: How Do Tumour Blood Vessels Form?mentioning
confidence: 99%
“…Stimulates proliferation and migration of cultured LECs Bjorndahl et al (2005a) IGFR-1 and -2 are present in lymphatic endothelium Induces growth of new LYVE-1 expressing lymphatic vessels in murine cornea metastasis via intra-and peritumourous lymphatic vessels Bjorndahl et al, 2005b). It appears that VEGF-A indirectly induces lymphangiogenesis by recruiting VEGFR-1 expressing inflammatory cells including monocytes/ macrophages and neutrophils that produce VEGF-C/-D because VEGFR-3 antagonists are able to block VEGF-A-induced lymphangiogenesis (Cursiefen et al, 2004).…”
Section: Igf-2mentioning
confidence: 99%
“…Thus, exposure of these growth factors to blood vessels and lymphatic vessels leads to simultaneous stimulation of angiogenesis and lymphangiogenesis (Cao, 2005b). However, under certain circumstances, both FGF-2 and VEGF-A have been reported to specifically induce only lymphangiogenesis and not angiogenesis (Chang et al, 2004;Bjorndahl et al, 2005b). The molecular mechanism underlying the differential effects of the same factor is currently unknown.…”
Section: Igf-2mentioning
confidence: 99%
“…Clinic pathological data from research using animal models indicates that tumor-induced lymphangiogenesis driven by vascular endothelial growth factor (VEGF)-C-and/or VEGF-D-induced activation of VEGF receptor (VEGFR)-3 could promote metastasis to regional lymph nodes. [5][6][7][8] Honokiol is a bioactive constituent isolated from the bark of Magnoliae. Previous reports have demonstrated that honokiol induces cell apoptosis in several cell lines, such as leukemia cell lines HL-60, colon cancer cell lines RKO, lung cancer cell lines A549 and CH27.…”
mentioning
confidence: 99%